2020
DOI: 10.1002/2211-5463.12783
|View full text |Cite
|
Sign up to set email alerts
|

NF‐kB signaling in cardiomyocytes is inhibited by sevoflurane and promoted by propofol

Abstract: Both inhalational and intravenous anesthetics affect myocardial remodeling, but the precise effect of each anesthetic on molecular signaling in myocardial remodeling is unknown. Here, we performed in silico analysis to investigate signaling alterations in cardiomyocytes induced by inhalational [sevoflurane (Sevo)] and intravenous [propofol (Prop)] anesthetics. Bioinformatics analysis revealed that nuclear factor‐kappa B (NF‐kB) signaling was inhibited by Sevo and promoted by Prop. Moreover, nuclear accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Several studies have reported that an HF diet is closely associated with inflammation [ 26 , 27 ]. NF-κB, one of the members in the family of transcription factors, often functions in most cells [ 28 ] and involves in the immune and inflammatory responses and affecting cell differentiation, apoptosis, and tissue damage [ 29 ]. It has been shown that an HF diet may induce high levels of IL-1β, IL-6, and TNFα by up-regulating the expression of TLR4 and NF-κB pathways [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that an HF diet is closely associated with inflammation [ 26 , 27 ]. NF-κB, one of the members in the family of transcription factors, often functions in most cells [ 28 ] and involves in the immune and inflammatory responses and affecting cell differentiation, apoptosis, and tissue damage [ 29 ]. It has been shown that an HF diet may induce high levels of IL-1β, IL-6, and TNFα by up-regulating the expression of TLR4 and NF-κB pathways [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…IPA was performed as described previously 24 , 25 . Briefly, molecules associated with shorter survival were analyzed by IPA software to search for canonical pathways.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the researches of Nrf2 in the central nervous system have become a hot spot (Liu et al, 2019;Shah et al, 2019). NF-κB is a family of dimeric transcription factors made up of five family members, p50 (NF-κB1), RelA (p65), p52 (NF-κB2), c-Rel, and RelB (Oda-Kawashima et al, 2020). Zhong et al (2014) revealed down-regulation of p65 was involved in the potential mechanisms of propofol-induced neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%